2022
DOI: 10.4102/sajcd.v69i2.910
|View full text |Cite
|
Sign up to set email alerts
|

Middle ear status – structure, function and pathology: A scoping review on middle ear status of COVID-19 positive patients

Abstract: Background: The coronavirus disease 2019 (COVID-19) pandemic is the latest public health emergency that has presented challenges globally. Limited evidence exists on the association between COVID-19 and middle ear pathologies, regardless of the respiratory nature of some of the core symptoms.Objective: This scoping review aimed at exploring evidence on the effects of COVID-19 on middle ear functioning as part of symptom mapping and preventive planning for ear and hearing care.Method: Electronic bibliographic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…However, only two cases with otitis media with effusion have shown the presence of the SARS-CoV-2 isolated from the middle ear, while other cases were tested positive for SARS-CoV-2 nucleic acid in the nasopharynx without certain evidence of SARS-CoV-2 infection in the middle ear [16] [17] [18] [19] [20]. Here, we report a group of outpatient cases in which the nucleic acid of SARS-CoV-2 was tested positively in the middle ear effusion, demonstrating the previous speculation that the SARS-CoV-2 can infect the middle ear [12] [21] [22] [23].…”
Section: Introductionsupporting
confidence: 65%
“…However, only two cases with otitis media with effusion have shown the presence of the SARS-CoV-2 isolated from the middle ear, while other cases were tested positive for SARS-CoV-2 nucleic acid in the nasopharynx without certain evidence of SARS-CoV-2 infection in the middle ear [16] [17] [18] [19] [20]. Here, we report a group of outpatient cases in which the nucleic acid of SARS-CoV-2 was tested positively in the middle ear effusion, demonstrating the previous speculation that the SARS-CoV-2 can infect the middle ear [12] [21] [22] [23].…”
Section: Introductionsupporting
confidence: 65%
“…In particular, Sebothoma et al reviewed eight studies that examined the effects of COVID-19 on middle ear function and found that middle ear-related symptoms, including otalgia and aural fullness, were common. In fact, among all symptoms, otalgia was the most common middle ear-related symptom reported in these eight studies [11]. This discrepancy may be related to differences in the sample sizes and patient ages.…”
Section: Discussionmentioning
confidence: 83%
“…Additionally, Karrim et al ( 2022 ) raised challenges with criteria, strategies and technical skills required for the utilisation of telerehabilitation by speech–language therapists and audiologists. For example, challenges were highlighted on telerehabilitation in children with autism spectrum disorder; middle ear assessments (Sebothoma & Khoza-Shangase, 2022 ); therapy for speech, language and swallowing following stroke (Tar-Mahomed & Kater, 2022 ); early communication intervention (Achmat & Gerber, 2022 ); neonatal feeding in neonatal intensive care units (Coutts et al, 2022 ); and geriatric audiology service provision in old age homes (De Andrade & Landman, 2022 ).…”
Section: Resultsmentioning
confidence: 99%